Dealing with Entrepreneurship Growth and Development in Creative Industry Yogyakarta: Coffee on the Bus Yogyakarta - Suseno Hendratmoko (PT FORMOSA CENDEKIA GLOBAL, 2023)
The evaluation of a business strategy represents one of the most important things a business agent must do to ensure the sustainability of an industry in a global marketplace. The Covid-19 pandemic, which lasted from 2020 to the world today, had a significant effect on the future viability of entrepreneurs. This marketing strategy was utilized as one of the business models to keep the company running. This study's design is descriptive qualitative. The purpose of descriptive qualitative research is to comprehend, describe, and reveal the conditions associated with the company's marketing strategy. Data analysis was finished through three stages: reduction, display, and verification. This study's design is descriptive qualitative. The purpose of descriptive qualitative research is to comprehend, describe, and reveal the conditions associated with the company's marketing strategy. An interview, observation, and study documents were used to collect data. Data analysis was finished through three stages: reduction, display, and verification